Eosinophilic Esophagitis - Update - Pathogenesis, Diagnosis and Therapy Eosinophile Ösophagitis - Neues zur Pathogenese, Diagnostik und Therapie - Von Arnim, Ulrike; Miehlke, S.; Madisch, A.; Vieth, M.; Straumann, A.; Malfertheiner, P. (Laryngo-Rhino-Otologie, 2017)
Eosinophilic esophagitis (EoE) is a clinicopathological condition of the esophagus that has become increasingly recognised over the last decade. EoE represents a chronic immune-mediated inflammatory disease of the esophagus. In adults dysphagia is the predominant symptom. Upper gastrointestinal endoscopy is required in order to take biopsies from the esophagus. The diagnose is confirmed histologically by typical eosinophilic infiltration of the esophagus mucosa. Until now there is no approved therapy world-wide although we know that topic and systemic steroids are highly effective in EoE. Elimination diet is another option and in well selected patients endoscopic balloon dilation represents a therapeutic possibility.
CRIS-Team Scopus Importer:2025-03-05
Keywords: eosinophilic esophagitis; esophagus; GERD